Medium chain triglycerides improve the growth performance, immune and antioxidant functions, and intestinal health of weaned rabbits. (21st December 2022) - Wang, Bin; Ye, Xin; Guo, Zhiqiang; Kuang, Liangde; Yang, Rui; Li, Congyan; Guo, Zihan; Zheng, Jie; Li, Yu Ying; Lei, Min; Lu, Jingzhi; Xie, Xiaohong
Abstract: The purpose is to study the effects of different doses of medium chain triglyceride (MCT) on growth performance, immune and oxidative functions, and intestinal health of weaned rabbits. A total of 600 weaned rabbits weighing about 993.26 g and at 35 d of age were randomly divided into five groups. The control group was fed a basal diet containing 2400 mg/kg soybean oil, and the experimental group was substituted with 600, 1200, 1800, and 2400 mg/kg MCT. The whole trial period lasted for 48 d. The results showed that treatment with 2400 mg/kg MCT significantly increased the weaning survival rate and crude fat digestibility ( p  < 0.05) and dramatically raised the levels of serum immunoglobulin (Ig)A, IgG, IgM, catalase, superoxide dismutase, and total antioxidant capability ( p  < 0.05). The villus height and crypt depth in 1800 mg/kg MCT group were observably enhanced ( p  < 0.05). The abundance of Bacteroidetes was significantly increased in 1800 and 2400 mg/kg MCT groups ( p  < 0.05). In conclusion, 1800 and 2400 mg/kg MCT substituting soybean oil in the diet of weaned rabbits can improve the growth performance and intestinal barrier function of weaned rabbits.